Sex-dependent vulnerability of fetal nonhuman primate cardiac mitochondria to moderate maternal nutrient reduction - Pereira, Susana P. (2021)
Poor maternal nutrition in pregnancy affects fetal development, predisposing offspring to cardiometabolic diseases. The role of mitochondria during fetal development on later-life cardiac dysfunction caused by maternal nutrient reduction (MNR) remains unexplored. We hypothesized that MNR during gestation causes fetal cardiac bioenergetic deficits, compromising cardiac mitochondrial metabolism and reserve capacity. To enable human translation, we developed a primate baboon model (Papio spp.) of moderate MNR in which mothers receive 70% of control nutrition during pregnancy, resulting in intrauterine growth restriction (IUGR) offspring and later exhibiting myocardial remodeling and heart failure at human equivalent ∼25 years. Term control and MNR baboon offspring were necropsied following cesarean-section, and left ventricle (LV) samples were collected. MNR adversely impacted fetal cardiac LV mitochondria in a sex-dependent fashion. Increased maternal plasma aspartate aminotransferase, creatine phosphokinase (CPK), and elevated cortisol levels in MNR concomitant with decreased blood insulin in male fetal MNR were measured. MNR resulted in a two-fold increase in fetal LV mitochondrial DNA (mtDNA). MNR resulted in increased transcripts for several respiratory chain (NDUFB8, UQCRC1, and cytochrome c) and adenosine triphosphate (ATP) synthase proteins. However, MNR fetal LV mitochondrial complex I and complex II/III activities were significantly decreased, possibly contributing to the 73% decreased ATP content and increased lipid peroxidation. MNR fetal LV showed mitochondria with sparse and disarranged cristae dysmorphology. Conclusion: MNR disruption of fetal cardiac mitochondrial fitness likely contributes to the documented developmental programming of adult cardiac dysfunction, indicating a programmed mitochondrial inability to deliver sufficient energy to cardiac tissues as a chronic mechanism for later-life heart failure.